2019
DOI: 10.1002/batt.201800121
|View full text |Cite
|
Sign up to set email alerts
|

A Zwitterionic Liquid Electrolyte for Magnesium Batteries

Abstract: Rechargeable magnesium batteries are promising energy storage devices due to their high theoretical capacity. However, currently a crucial hindrance for their realization is the limited number of suitable electrolytes, all of which show severe disadvantages. We circumvent volatility, flammability, and instability issues of other systems by presenting an electrolyte based on magnesium borohydride and the zwitterionic liquid (ZIL) 1‐butyl‐3‐methylimidazol‐2‐ylidene borane. We investigate the structure and proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ren et al proposed a mechanism of competitive coordination of [Tf 2 N] – to dramatically increase the current density of Mg plating/stripping. In addition to the use of conventional ionic liquids, a zwitterionic liquid, 1-butyl-3-methylimidazol-2-ylidene borane, was initially investigated by Tröger-Müller and Liedel as the electrolyte system, performing higher reversibility and stability than the isostructural [BMIM]­[Tf 2 N] ([BMIM] + = 1-butyl-3-methyl-imidazolium). Furthermore, Gao and co-workers , extended their concept from a previous study, achieving reversible Mg plating/stripping with alkoxy functionalized ILs, and demonstrated a remarkable Ca/V 2 O 5 cell using (Ca­[BH 4 ] 2 ) 0.05 ([N 07 ]­[Tf 2 N]) 0.95 , where the alkoxy-functionalized ammonium cation ([N 07 ] + = N , N , N -tri-(2-(2-methoxyethoxy)­ethyl)- N -(2-methoxyethyl)­ammonium) was revealed that effectively optimizes the calcium coordination sphere for the high reversibility.…”
Section: Electrochemical Energy Storagementioning
confidence: 99%
“…Ren et al proposed a mechanism of competitive coordination of [Tf 2 N] – to dramatically increase the current density of Mg plating/stripping. In addition to the use of conventional ionic liquids, a zwitterionic liquid, 1-butyl-3-methylimidazol-2-ylidene borane, was initially investigated by Tröger-Müller and Liedel as the electrolyte system, performing higher reversibility and stability than the isostructural [BMIM]­[Tf 2 N] ([BMIM] + = 1-butyl-3-methyl-imidazolium). Furthermore, Gao and co-workers , extended their concept from a previous study, achieving reversible Mg plating/stripping with alkoxy functionalized ILs, and demonstrated a remarkable Ca/V 2 O 5 cell using (Ca­[BH 4 ] 2 ) 0.05 ([N 07 ]­[Tf 2 N]) 0.95 , where the alkoxy-functionalized ammonium cation ([N 07 ] + = N , N , N -tri-(2-(2-methoxyethoxy)­ethyl)- N -(2-methoxyethyl)­ammonium) was revealed that effectively optimizes the calcium coordination sphere for the high reversibility.…”
Section: Electrochemical Energy Storagementioning
confidence: 99%
“…To circumvent this issue, a protecting group may be introduced after synthesis, for example upon formation of an N‐heterocyclic carbene (NHC) borane in an easy way . The resulting zwitterions indeed show superior reductive stability and have recently been described as the solvent component in the electrolyte of magnesium batteries . Applying this approach of forming an NHC borane to truly sustainable imidazolium ionic liquids may consequently also lead to the use of sustainable imidazolium‐type ionic liquids in electrolytes for magnesium‐ion batteries.…”
Section: Electrolytes and Separatorsmentioning
confidence: 99%
“…However, they still face many challenges, such as high prices, a scarcity of resources, and safety issues. It is predicted that LIBs might not be able to meet the needs of road transport electrification in the near future . Rechargeable magnesium batteries (RMBs), as a sustainable energy storage system, have recently attracted attention as a beyond lithium battery owing to the low price of magnesium, potential stability in air, high theoretical volumetric capacity (∼3833 vs 2062 mAh cm –3 for Li) and the low reduction potential (−2.4 V vs SHE). , Despite these positive features, there are two major challenges that need to be overcome before realizing practical RMBs.…”
Section: Introductionmentioning
confidence: 99%